Educação de jovens e adultos teoria, práticas e políticas - Miguel, José Carlos (Editora Oficina Universitária, 2022)
The book "Education of Young People and Adults: Theory, Practices and Policies" aims to discuss theoretical principles of pedagogical practice, educator training and public policies in this area of knowledge. It results from actions aimed at minimizing the enormous social debt of illiteracy and the desirable articulation between teaching, research and university extension, increasing the process of initial and continued teacher training, in order to combine theory and practice. It is understood that in Human Sciences, research is consolidated from the university extension at the same time that a dialogue is established with the society that subsidizes the university. Basically, the studies are guided by Bakhtin's dialogical perspective and by the assumptions of the cultural-historical theory, a vast range of theoretical principles inherent in the thought of Vygotsky and followers, and Paulo Freire's educational perspective constitutes a reference for Philosophy of Education. Education. It is a process of searching for the construction of a theoretical identity for the education of young people and adults whose fundamental pedagogical principle is the incorporation of the culture and the experiential reality of the students as content or starting point of the educational practice. It is imperative to thematize the relationships between thought and language, between thought and culture, between oral culture and written culture, and between spontaneous concepts and scientific concepts. And to think from the methodological perspective of problem solving, which requires thinking about the formation of an epistemologically curious teacher, as Paulo Freire teaches us. Thus, the book is of interest for the initial training of teachers, for teachers who teach in EJA and for professionals in education networks involved with technical-pedagogical guidance and initial or continuing training of educators.